2011
DOI: 10.1186/1471-2458-11-796
|View full text |Cite
|
Sign up to set email alerts
|

Newspaper coverage of mental illness in the UK, 1992-2008

Abstract: BackgroundRecent years have seen a number of attempts to reduce the stigma related to mental illness; the media can play a significant role in perpetuating this stigma. This paper analyses trends in newspaper coverage of mental illness in the UK between 1992-2008 across a range of psychiatric diagnoses.MethodsA content analysis was performed on a sample of articles (n = 1361) about mental illness in a range of UK newspapers in 1992, 2000, and 2008.ResultsThere was a significant proportional reduction in negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
4
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 22 publications
10
75
4
5
Order By: Relevance
“…Previous studies in Japan, Australia, and the United States have highlighted that a large part of the general population held stereotypes that individuals with schizophrenia were dangerous (Corrigan et al, 2002;Griffiths et al, 2006). In newspapers, 14-49% of articles on mental illness were linked to danger (Goulden et al, 2011;Magliano et al, 2011;Nawkova et al, 2012;Whitley and Berry, 2013). Furthermore, newspaper coverage of schizophrenia has been shown to be disproportionately negative compared with other psychiatric conditions in previous studies in the United Kingdom (Goulden et al, 2011;Thornicroft et al, 2013), Belgium (Thys et al, 2013), Czech Republic, Croatia, and Slovakia (Nawkova et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies in Japan, Australia, and the United States have highlighted that a large part of the general population held stereotypes that individuals with schizophrenia were dangerous (Corrigan et al, 2002;Griffiths et al, 2006). In newspapers, 14-49% of articles on mental illness were linked to danger (Goulden et al, 2011;Magliano et al, 2011;Nawkova et al, 2012;Whitley and Berry, 2013). Furthermore, newspaper coverage of schizophrenia has been shown to be disproportionately negative compared with other psychiatric conditions in previous studies in the United Kingdom (Goulden et al, 2011;Thornicroft et al, 2013), Belgium (Thys et al, 2013), Czech Republic, Croatia, and Slovakia (Nawkova et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…For example, the number of outpatients using psychiatry services in Japan has almost doubled (Ministry of Health, Labour andWelfare, 1990-2011). A previous study in the United Kingdom demonstrated that the number of articles on mental illnesses has also almost doubled from 1992 to 2008 (Goulden et al, 2011). These factors may confound time-related changes in the social attitudes specific to schizophrenia.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Persons with mental illness are often portrayed in media coverage as being incompetent (Goulden et al, 2011) or "helpless, disempowered and child-like" (Olstead, 2002, p. 634). Furthermore, despite mental illness being a common feature of everyday life, news reports about persons with mental illness often focus on rare, violent events (The Carter Center, 2015).…”
Section: Introductionmentioning
confidence: 99%